Homeostatic structural plasticity can account for topology changes following deafferentation and focal stroke - Butz, Markus; Steenbuck, Ines D.; van Ooyen, Arjen (Frontiers in Neuroanatomy, 2014)
After brain lesions caused by tumors or stroke, or after lasting loss of input (deafferentation), inter- and intra-regional brain networks respond with complex changes in topology. Not only areas directly affected by the lesion but also regions remote from the lesion site may alter their connectivity---a phenomenon known as diaschisis. Changes in network topology after brain lesions can lead to cognitive decline and increasing functional disability. However, the principles governing changes in network topology are poorly understood. Here, we investigated whether homeostatic structural plasticity can account for changes in network topology after deafferentation and brain lesions. Homeostatic structural plasticity postulates that neurons aim to maintain a desired level of electrical activity by deleting synapses when their activity is too high and by providing new synaptic contacts when their activity becomes too low. Using our Model of Structural Plasticity, we explored the consequences of local changes in connectivity induced by a focal loss of input for global network topology. In accordance with experimental and clinical data, we found that after partial deafferentation, the model network as a whole became more random, although it maintained its small-world topology, while deafferentated neurons increased their betweenness centrality as they rewired and returned to the homeostatic range of activity. Furthermore, their degree distributions became more tailed, indicating the emergence of hub neurons. Deafferented neurons also showed an increase in their global but a decrease in their local efficiency. Together, our results suggest that homeostatic structural plasticity may be an important driving force for lesion-induced network reorganization. Computational models with structural plasticity may therefore provide novel insights into the mechanics of brain recovery and inspire novel treatments of brain damage.